Polarization characteristics of standing wave electromagnetic fields at the ionospheric Alfvén resonator lower harmonics: altitude profiles - Prikner, K. (Karel); Feygin, F. Z.; Raita, T. (Studia Geophysica et Geodaetica, 2014)
This paper is an illustrative addition to the paper by Prikner et al. (2014) in this issue. Electromagnetic ion-cyclotron waves (EMIC waves) propagating from the magnetosphere into the ionosphere generate non-propagating standing wave electromagnetic fields. They occur in the whole altitude domain of the ionospheric Alfvén resonator (IAR).